Perspective of the family in the daily life with the squizo’s porter - Emanuel Martins da Silva; Maria Salete Bessa Jorge; Maria Veraci Oliveira Queiroz (Rev Rene)
The family has an essential function in the process of psychosocial rehabilitation of his member with squinzo’s diagnosis, cause he take part of health and sickening of the group. We objective to understand the living of the family with the member of squizo’s porter. Qualitative study with assumptions of Symbolic Interactionism. It was developed in an hospital-day headed to the attendance in mental health in municipal of Fortaleza-Ceará. Took part of the study five relatives identified during the assistance of his relative with squizo’s diagnosis. We used the participant observation and the interview semi-structured. In the analysis/interpretation the families shown to notice the mental breakdown as a far and not contextualized of itself phenomena. They refer that the knowledge acquired in reunions with professional as well as trades of informations with others families, help in the living with his relative. It is important the professional intervention as in the porter of squizo’s diagnosis as his family.